GO GREEN SCHOOLl, UPAYA PENYADARAN PEDULI LINGKUNGAN BAGI SISWA SMA KOTA MEDAN - Sularno Sularno; Tri Martial (Jurnal Pengabdian Mitra Masyarakat, 2021)
Go green school program is to create good conditions for schools to be a place of learning and awareness of the school community, so that teachers and students can share responsibility in the effort to save the environment and sustainable development of the school is expected to create and maintain schools that have environmental and sanitary clean, healthy, comfortable and shady with trees. But in reality, the school community to create awareness of environmentally friendly behavior are still facing obstacles. Some problems in the school is the limited human resources to implement the program GGS (both teachers and students), there is no group of activists go green school of students, lack of awareness and knowledge of the school community in the management of organic and inorganic waste, lack of knowledge of process organic waste into organic fertilizers, the limited open space that can be planted with trees, a lack of knowledge of the choice of plants that suit the environment, the limitations of infrastructure and funding for the implementation of programs go green school.To overcome these problems do community service through IbM program with one or two partners namely SMA AnNizam  and SMA Muhammadiyah 2 Medan. Team Community Service Faculty of Teacher Training and Education UISU will do counseling, training, creation of organic fertilizer or compost, formed a task force to go green school students, planting potted plant species adapted to the conditions of the school environment.  With IbM go green school program, is expected to partner schools can overcome the obstacles encountered thus changing the behavior of people in schools that are environmentally friendly and can run a green school program.